Topical Polydeoxyribonucleotide Loaded in Hydrogel Formulation for Wound Healing in Diabetic Rats - Dmitriyeva, Mariya; Suleimenov, Timur; Yessenbayev, Daulet; Turebayev, Dulat; Urazova, Saltanat; Izimbergenov, Mirsaid; Kozhakhmetov, Saken; Omarov, Talgat; Toleubayev, Medet (Open Access Macedonian Journal of Medical Sciences, 2022)
Patients with diabetes mellitus experience delayed wound healing because of the uncontrolled glucose level leads to impaired cell proliferative function, poor circulation, decreased production and repair of new blood vessels. Polydeoxyribonucleotide (PDRN) is used in wound healing as a substance that stimulates tissue repair. A hydrogel is a reticular substance generally used as a dressing formulation to accelerate wound healing, and also used as a bio-applicable scaffold or vehicle. The aim of study is to investigate the effects of PDRN loaded in hydrogel on wound healing, in combination and separately, in an animal diabetic wound model. Methods: We studied the effects of PDRN in diabetes-related healing defect using an incisional skin-wound model produced on the back of male diabetic rats. A total of 36 wounds, were classified into 3 groups: a control group, a hydrogel-only group, a PDRN loaded in hydrogel combined-treatment group. All rats were assessed for changes in wound size and photographed on scheduled dates. The skin specimen sample of diabetic rat wound model were observed on 3, 7, 14 and 21 days after skin injury to measure tissue remodeling through histological evaluation of fibroblasts proliferation, and collagen production, also the number of blood vessels was measured in all specimens. Results: Differences in the decrease and change in wound size in the PDRN loaded in hydrogel group were more significant than those in the control and hydrogel single-treatment groups. Analysis of the fibroblasts proliferation, collagen production and number of blood vessels through histological examination showed a pattern of increase over time that occurred in PDRN loaded in hydrogel combined-treatment group. Conclusion: This experiment demonstrated improved wound healing using a PDRN loaded in hydrogel combined treatment compared to either two groups, resulting in a decrease in diabetic wound size and a shortening of the healing period